Estratégias de design aplicadas a territórios para o fortalecimento e a prospecção turística de indicações geográficas: um estudo a partir da IP Altos Montes/RS - Engelmann, Marcos Eduardo (Universidade do Vale do Rio dos Sinos, 2023)
Obtaining a geographical indication (GI) is an important step in recognizing, promoting and protecting the origin of a product. Such economic benefits can be extended to other members of the territory through tourism, but for that, it is essential that some strategies are developed, considering that only the GI is not enough to achieve this. In this sense, the strategic design favors the construction of a collaborative and future vision, in which the actors, their behaviors and their practices are contemplated. These elements make it possible to design a new reality, offering society to the market a system of processes, research, methods, beliefs, values and tools. Thus, the main objective of this research is to develop design guidelines that enhance, through Strategic Design, tourism in regions that have recently obtained a geographical indication (GI). The IP Altos Montes was chosen as the object of study because it is a geographical indication close to Bento Gonçalves - RS, but which has not yet achieved the same success in terms of tourist development as this city. From a theoretical review, added to the analysis of case studies, syntheses of seminars on wine tourism and field studies, 51 design guidelines were developed that can be used in the design and implementation of different strategies for tourist projection of a geographical indication. A metaprojectual experiment was also carried out, which proposed a territorial positioning and eight future scenarios to boost IP Altos Montes. The research seeks to contribute to the social and economic development of regions that obtained a geographical indication, using a territorial study in which all the integrating agents are contemplated. From an academic perspective, this research contributes to Strategic Design, showing, through applied research, the use of territorial design in a tourist context, evidencing the migration of the field of action to a broader context.
Keywords: Design estratégico; Ecossistemas turísticos; Enoturismo; Indicações geográficas; Territórios; Turismo; Geographical indications; Strategic design; Territories; Tourism ecosystems; Tourism; Wine tourism; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial